Gambaran Hasil Pemeriksaan Jumlah Eosinofil pada Penduduk di Sekitar Stockpile Batu Bara Kabupaten Muaro Jambi - Dewi Kurniasih; Muslina Muslina; Aminahtun Latifah (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Coal as a fuel is used in the industrial sector which indirectly causes air pollution which has broad toxic effects on humans, one of which is disturbance on blood profile. White blood cells (leukocytes) in the human body's defense system play a role in resistance to foreign substances. Eosinophils are a type of leukocyte that function as the body's defense, especially in parasitic infections. Based on observations made, the coal stockpile in Muaro Jambi is still included in the residential area which of course has a direct impact on the health of the surrounding population. The research was conducted descriptively with a cross sectional approach involving 30 residents living around the stockpile of Muaro Jambi. Data of eosinophils count was obtained from the results of blood tests using the automatic method with a Hematology Analyzer. From the the study, the average of examination eosinophils result were within the normal range (3.15). With a higher average for men (3.90), the distance from the house to the stockpile location is â‰¤ 500 meters (3.47) and the length of domicile shows that the length of stay is â‰¥ 10 years (3.23). The results of examining eosinophils result in residents around the stockpile indicate that the average value is normal, with a higher value in respondents with spesific characteristics.